All polarization-maintain fiber mode-locked laser based on nonlinear polarization evolution. (18th August 2021) - Li, Hongxun; Dong, Zhipeng; Zhang, Yimin; Tao, Runxia; Lin, Jiaqiang; Gu, Chun; Yao, Peijun; Xu, Lixin; Zhang, Rui; Su, Jingqin
Abstract: We propose and demonstrate an all polarization-maintain fiber (PMF) mode-locked laser based on nonlinear polarization evolution without any splicing angle. In this laser, the complex optimization of the fused splicing angle between PMFs can be avoided and high modulation depth is achieved through using a special polarization beam splitter. By simply adjusting pump power, the environmentally stable dissipative-soliton-resonance pulse train is self-started, which is a challenge for nonlinear-amplifying-loop-mirror systems. Our work has great potential in high-energy pulse source as well as ultrafast and high-repetition-frequency laser source using dispersion compensation and high nonlinear fibers.